Mathematics pre-service teacher's metacognitive failure in mathematics online learning - Alifiani Alifiani; Surya Sari Faradiba (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2021)
This study aims to reveal the metacognitive failures experienced by mathematics pre-service teachers based on their mistakes when solving problems in online learning during the pandemic era. This case study involved 29 participants who attended the mathematical problem test and cognitive style test, the two participants were categorized based on their cognitive style: Field Dependence (FD) and Field Independence (FI). The instrument used was a mathematical problem test to collect data on metacognitive that adapted from Stewart and a cognitive styles test to categorize the cognitive style that adapted from the Group Embedded Figures Test (GEFT). An interview was conducted to determine the nature of mathematical error based on metacognitive failure. The description of data analysis and interpretation of the meaning of the findings applied the text analysis. The results showed the different metacognitive failures of the two participants. The metacognitive failure of FI student was categorized as metacognitive blindness and the FD student was categorized as metacognitive stagnation, a new condition of metacognitive failure that was found in this study.